Warsztat malarski cyklu obrazów emporowych z kościoła pod wezwaniem św. Jana w Gdańsku - Olszewska-Świetlik, Justyna; Pawlak, Ewelina (Acta Universitatis Nicolai Copernici Zabytkoznawstwo i Konserwatorstwo, 2011)
The article presents issues concerning the techniques used by the painting workshop commissioned to make a cycle of paintings (dating 1666) which decorate the choir gallery in St John’s Church in Gdańsk. The technical specification of the paintings as well as the identification of the painting materials were carried out by means of mutually supplementary modern physical methods, including microscopic, chemical and instrumental examinations. The analyses of the technology and painting techniques of the paintings in question show that they came from a local guild workshop. The evident differences in the artistic level indicate that the paintings were made by several craftsmen, which was typical of big painting workshops of the time. The workshop used a variety of techniques characteristic of 17th – century painting, such as the use of linen painting basis, oil binder, dark red priming ground, as well as the use of formers in the process of creating a painting. (In this particular case, the inspiration came from the drawings by Matthew Meriana the Older, to be found in a Lutheran Bible printed in Strasburg in 1630 by the printing house of Lazarus Zetzner.) The workshop used special mixtures of paints for individual parts of a painting, together with grey underpainting layer and multi-layer modelling. It has been found that, with respect to both the content and the painting techniques, the choir gallery paintings from St John’s Church in Gdańsk manifest features typical of the guild painting of the northern school of the second half of the seventeenth century.